2018
DOI: 10.1109/tcsvt.2017.2764868
|View full text |Cite
|
Sign up to set email alerts
|

Activity Recognition in Sensor Data Streams for Active and Assisted Living Environments

Abstract: In active and assisted living environments, a major service that can be provided is the automated assessment of elderly people's well-being. Therefore, activity recognition is required to detect what types of help disabled persons need to support them in their daily life activities. Unfortunately, it is still a difficult task to estimate the size of the required window for online sensor data streams to recognize a specific activity, especially when new sensor events are recorded. This paper proposes a windowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…In their research, the authors of these papers implement various types of sensors, according to their purposes, namely: indoor sensors [1], occupancy information sensors [1], electricity meters [1,6,44], motion sensors [6,7,30,59,60], item kitchen sensors [6], door sensors [6,59,61,62], temperature sensors [1,2,6,59,63], photosensors [1,3,63], status of water and burner sensors [6,59], acceleration sensors [4,7], Kinect motion sensors [7], modern smartphone sensors [4,7,60], passive radar-based sensors [8], unobtrusive sensors [9,14], infrared sensors [15,30], wireless sensor networks [61,62], accelerometers [5,63], altimeters [63], gyroscopes [63], barometers [63], heart rate monitor [63], embedded sensors [4,…”
Section: Classificationmentioning
confidence: 99%
See 4 more Smart Citations
“…In their research, the authors of these papers implement various types of sensors, according to their purposes, namely: indoor sensors [1], occupancy information sensors [1], electricity meters [1,6,44], motion sensors [6,7,30,59,60], item kitchen sensors [6], door sensors [6,59,61,62], temperature sensors [1,2,6,59,63], photosensors [1,3,63], status of water and burner sensors [6,59], acceleration sensors [4,7], Kinect motion sensors [7], modern smartphone sensors [4,7,60], passive radar-based sensors [8], unobtrusive sensors [9,14], infrared sensors [15,30], wireless sensor networks [61,62], accelerometers [5,63], altimeters [63], gyroscopes [63], barometers [63], heart rate monitor [63], embedded sensors [4,…”
Section: Classificationmentioning
confidence: 99%
“…With respect to the reasons for using the SVM method with sensor equipment in smart buildings, it can be observed that the recognition of human activity is at the forefront, as this is addressed in most of the papers [3,4,6,[8][9][10]14,15,[29][30][31][32]59,60,62,63]. Assisted living was a strong motivation for using the SVM method with sensor devices in the smart buildings sector; seven of the identified papers focusing on the recognition of human activity did so in order to provide appropriate assisted living [6,14,15,[30][31][32]63], while other papers aimed to achieve assisted living by focusing on human fall detection [7], human behavior recognition [2], assessment of occupancy status information, and identification of human behavior [61]. Other reasons for applying SVM with sensors in smart buildings include measuring the occupancy status of a building's inhabitants in order to improve the energy prediction performance of the building's energy model [1], classifying the gender of occupants [5], forecasting electricity consumption [44], detecting and classifying human behavior with a view to maximizing comfort with optimized energy consumption [52], recognizing household appliances in order to assess their usage and develop habits of power preservation [64], and selecting optimal sensors for use in complex system monitoring problems such as HVAC chillers [65].…”
Section: Classificationmentioning
confidence: 99%
See 3 more Smart Citations